Performance of defected ground structure for rectangular microstrip patch antenna - Sh-Ali, Jamal Muhiyadin (2015)
In wireless communications systems, harmonics and unwanted frequency other than designed one becomes a dominant factor in limiting quality and capacity of transmitted or received signal. Rectangular microstrip patch antenna (RMPA) is designed in order to obtain the required parameter responses at 2 GHz. The proposed antenna is excited through the microstrip feed line which is connected directly to the patch antenna. RMPA of length 35.8462 mm and width 46.0721 is designed on the substrate dielectric material FR-4 having dielectric constant r=4.3 and thickness 1.6 mm. The defect ground structure (DGS) has gained much attention over the last few years for its ability to increase the performance of wireless system by effectively suppressing harmonics DGS shows a better result compared to the conventional antenna. It effectively suppressing spurious frequency and reduces the amplitude of the unwanted multiple bands since the antenna radiates only one resonating frequency.